Bridging theory and practice: how open distance learning fosters ESL teachers’ professional growth in Malaysia - Li Hsien Ooi; Juliana Othman (AAOU Journal)
Purpose – This research aims to investigate the role played by open distance learning (ODL) in supporting the professional development of in-service teachers in the field of English as a Second Language (ESL) at a Malaysian higher education institution. In a rapidly evolving educational landscape, continuous professional development is essential for teachers, particularly for underqualified in-service educators. ODL offers a flexible and accessible pathway that allows teachers to simultaneously pursue academic qualifications while fulfiling their professional and personal responsibilities. Design/methodology/approach – This study employed a qualitative case study design to examine how ODL influences pedagogical practices. Data were gathered through in-depth interviews with four in-service ESL teachers enrolled in an undergraduate Teaching English as a Second Language (TESL) programme delivered via ODL. Findings – A thematic analysis of the interview data revealed several key insights. The flexibility of ODL allowed participants to balance their work, study and personal responsibilities, although effective time management was critical for success. The programme facilitated the integration of theoretical knowledge with classroom practices and improved instructional strategies. However, some participants found it challenging to apply abstract theories in real-world teaching contexts. Although ODL enabled the immediate implementation of newly acquired techniques, an inadequate technological infrastructure hindered this process. Expert guidance was valuable, yet limited face-to-face interaction posed challenges for some educators. Practical implications – The findings offer valuable insights for policymakers and ODL institutions. They highlight the need for strengthened institutional support, improved technological infrastructure and enhanced interactive learning opportunities. Originality/value – This study highlights the need for enhanced support systems, targeted professional development strategies and policy measures to improve teachers’ effectiveness.